Pengaruh Terapi Massage Effleurage Terhadap Nyeri Punggung Pada Ibu Hamil Trimester III - Mardiani, Norma; Resna, Mia Novia (Program Studi Kesehatan Masyarakat Universitas Sari Mutiara Indonesia, 2022)
Back pain that occurs for a long time and is not treated immediately, can lead to long-term back pain, increasing the tendency for postpartum back pain, and chronic back pain that will be more difficult to treat or cure. Massage therapy is one of the non-pharmacological therapies that can reduce back pain for pregnant women, massage will reduce muscle tension and pain, increase mobility and improve blood circulation. Analyzing the effect of effleurage massage on back pain in third trimester pregnant women. The research method used is pre-experiment with a one-group pretest-posttest design approach. The population in this study were all pregnant women at Kaliwadas Health Center with a gestational age of 32 weeks and above in January - March 2022 totaling 42 populations, while the sample taken was 16 respondents. Hypothesis test using Mann Withney test. The level of back pain before being given Massage Effleurage therapy had an average of 2.56 and after being given Massage Effleurage therapy had an average of 1.87. This means that there is a decrease in the level of back pain after being given Massage Effleurage therapy of 0.69. The results of the Mann Withney test obtained the Asymp value. Sig. of 0.021, so Ha is accepted, which means it can be concluded that there is an effect of Massage Effleurage on back pain in third trimester pregnant women at Kaliwadas Health Center. There is an effect of Massage Effleurage on back pain in third trimester pregnant women at Kaliwadas Health Center.